2014
DOI: 10.4103/2230-8598.144107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of counseling on temporarily deferred donor in a tertiary care hospital, central India: A prospective study

Abstract: Background: Donors disqualifi ed or rejected from donating blood are known as "deferred" donors. Blood donors are deferred for various reasons. Donors are deferred either temporarily or permanently. To make blood transfusion safe for the patients, many safety measures are undertaken, and the most important is a selection of the suitable blood donors. The rate and reasons of deferral differ from region to region and one center to the other. Aim: The aim of this study is to fi nd out the impact of counseling on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, substantially higher deferral rates have also been reported elsewhere, including 22.5% in Brazil 15 , 30.9% in Iran 16 , and 35.6% in Trindad and Tobago 17 . In India, there is a wide range in deferral rates, from 2.5% to 33.0%, although most studies report low figures (median = 6.2%) 18,19,20,21,22,23 .…”
Section: Rates and Types Of Deferralsmentioning
confidence: 99%
“…However, substantially higher deferral rates have also been reported elsewhere, including 22.5% in Brazil 15 , 30.9% in Iran 16 , and 35.6% in Trindad and Tobago 17 . In India, there is a wide range in deferral rates, from 2.5% to 33.0%, although most studies report low figures (median = 6.2%) 18,19,20,21,22,23 .…”
Section: Rates and Types Of Deferralsmentioning
confidence: 99%
“…The donors who were not suitable standard operating procedure (SOP) criteria, NABH and National Blood deferred donor or temporary deferred to donate blood at that time, according to the based on the food and drug administration policy were deferred. [4][5][6][7] Pre-donation temporary deferrals were coded and divided into categories covering all main causes of donor rejection and depending on the reasons of deferral; the deferral period was defined for the donor to come back for blood donation.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] This study showed , average age among the male and female blood donors were not different and mean age found 29±6 and 29±7 , according to the male and female respectively, which matched with other study , where mean age was about 29±6. [7][8][9] But among non-rejected and rejected replacement blood donors both systolic and diastolic blood pressures were lower in deferral donors in comparison to its successful participants. Thus our study differed with Arslan (2007) , a study conducted among Turkish donors, where, main reason for their deferral was common cold or elevated temperature (20·4%) among male and low haemoglobin (51·6%) in female.…”
Section: Discussionmentioning
confidence: 99%
“…5,[10][11][12][13][14][15] This present study showed, diastolic and systolic blood pressures were lower among deferral donors according to guideline [1][2][3]18 compared to normal successful counterparts , thus present study differed with other studies on donor deferral. [8][9][10][11][12][13][14][15] Finally, minimum (10.72%) female participation with majority female donor rejection emphasized that, further evaluation, motivation and clinical assessment on female blood donors are recommended.…”
Section: Discussionmentioning
confidence: 99%